2022
DOI: 10.1186/s12888-022-03849-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of shared decision making among patients with psychotic disorders in Norway: a qualitative study

Abstract: Background Shared decision making (SDM) is a process where the patient and the health professional collaborate to make decisions based on both the patient’s preferences and the best available evidence. Patients with psychotic disorders are less involved in making decisions than they would like. More knowledge of these patients’ experiences of SDM may improve implementation. The study aim was to describe and explore experiences of SDM among patients with psychotic disorders in mental health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Shared decision-making (SDM) models, an approach in which patients and providers collaborate to make health care decisions based on patient preference and the best available evidence, have been recommended for use with people with PSDs (Charles et al, 1997). SDM is associated with patient satisfaction and fewer decision conflicts (Haugom et al, 2022). However, researchers have shown SDM to be inconsistently implemented among patients with PSDs, particularly those who have experienced involuntary treatment (Drivenes et al, 2020) despite patients’ positive responses to SDM (Haugom et al, 2022).…”
Section: Therapeutic Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Shared decision-making (SDM) models, an approach in which patients and providers collaborate to make health care decisions based on patient preference and the best available evidence, have been recommended for use with people with PSDs (Charles et al, 1997). SDM is associated with patient satisfaction and fewer decision conflicts (Haugom et al, 2022). However, researchers have shown SDM to be inconsistently implemented among patients with PSDs, particularly those who have experienced involuntary treatment (Drivenes et al, 2020) despite patients’ positive responses to SDM (Haugom et al, 2022).…”
Section: Therapeutic Assessmentmentioning
confidence: 99%
“…SDM is associated with patient satisfaction and fewer decision conflicts (Haugom et al, 2022). However, researchers have shown SDM to be inconsistently implemented among patients with PSDs, particularly those who have experienced involuntary treatment (Drivenes et al, 2020) despite patients’ positive responses to SDM (Haugom et al, 2022). This is likely due to barriers such as providers’ parentalistic approach to care and beliefs that patients with PSD cannot feasibly or thoughtfully partake in SDM (Zisman-Ilani et al, 2017).…”
Section: Therapeutic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,8] Research has shown that the practice of SDM is highly acceptable amongst patients with enduring psychotic illnesses and psychiatrists, [9,10,11] although differences in attitudes towards and subsequent participation in SDM have been identified in the case of the latter. [12] However, the practice of SDM has yet to be successfully adopted for routine use in psychiatric settings amongst patients with severe mental illnesses. [13] Suboptimal rates of SDM adoption are particularly prominent during antipsychotic treatment decisions amongst patients with psychotic illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving mental health care in Norway have the right, as far as is reasonable, to choose between different mental health treatment options, including treatment without medication [ 23 ], such as family interventions or cognitive behavioural therapy [ 24 , 25 ]. Despite this, recent studies show that SDM for patients with psychotic disorders is often limited to making choices between different types of antipsychotic medication [ 26 , 27 ]. This highlights the importance of examining the association between SDM and patients’ perceptions of being respected for their desire not to use medication.…”
Section: Introductionmentioning
confidence: 99%